Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1088/0967-3334/27/7/006
|View full text |Cite
|
Sign up to set email alerts
|

Storage effects on the Cole-Cole parameters of erythrocyte suspensions

Abstract: Chemical alterations of red blood cells (RBCs) during storage eventually affect the electrical properties of blood. In this study, the physiological parameters such as extracellular (SAGM + CPD + residual plasma) Na(+), K(+), Cl(-), pH, 2,3-DPG and ATP together with the Cole-Cole parameters were measured using erythrocyte suspensions from 51 male donors (31 donors form the training set and 20 donors are used for testing), on the 0th, 10th, 21st, 35th and 42nd days of storage. During storage, while the surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…While Cl -ions enter the cell, bicarbonate ions leave the cell [4], [6]. The cell swells with Cl -and a shape change occurs from discocyte to spheroechinocyte shape, resulting in an increased form factor [9]. The extracellular resistance is inversely proportional to this form factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Cl -ions enter the cell, bicarbonate ions leave the cell [4], [6]. The cell swells with Cl -and a shape change occurs from discocyte to spheroechinocyte shape, resulting in an increased form factor [9]. The extracellular resistance is inversely proportional to this form factor.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological and electrical measurements of erythrocyte suspensions were performed at room temperature [9].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies reported that K + , 2,3-BPG, ATP, and pH values in stored blood and blood components change with time, and research has been conducted in an effort to increase the quality of stored blood [24,25,26,27,28,29,30]. Studies on the biochemical and hematological properties of stored UCB, however, are less common,[26,27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the biochemical and hematological properties of stored UCB, however, are less common,[26,27,28,29,30]. Studies on the biochemical and hematological properties of stored UCB, however, are less common.…”
Section: Discussionmentioning
confidence: 99%
“…3), the extracellular Na + , K + and Cl -concentrations, 2,3-DPG, ATP and pH were measured at room temperature as described in the earlier study [36].…”
Section: Biochemical Measurementsmentioning
confidence: 99%